A dimensão ambiental nos instrumentos de planejamento urbano no município de Toledo/PR - Nogueira, Daiana Cristina Gomes (2017)
The difficulty and the proportion that the environmental problems have acquired in the last decades have required a lot of effort to revert to the constant degradation of the environment and its ecosystem. When we consider water resources, the impacts are even more intense, it is because all the activities, domestics, rural and industrial need it to their development. The wellspring conservation requires constant knowledge and monitoring; developing environment public policies, thus possible to reach the sustainability level that today is spread in the global discussions. This job allows us to analysis the environmental dimension in the Toledo’s urban planning and how the public management builds its actions and strategies to integrate the environment in urban areas around the Toledo River Basin. To reach the objectives, a qualitative approach through documentary analysis was carried out together with a bibliographical revision referring to the proposed theme. An exploratory analysis around the Toledo River diagnosed some buildings and several environmental problems that are already present in this area. Data were collected from the City Hall of Toledo, IBGE, SANEPAR and the Municipal Council of the Environment. The conclusions that were presented converge towards the concept elaboration of urban environmental management, contributing to a necessary review of the implementation of urban and environmental management tools, with a view to adoption of crosscutting logic - quality essential for the urban sustainability construction, therefore to sustainable development. As recommended, this paper presents an elaboration of an ENVIRONMENTAL PLAN, which can be prepared with the Master Plan, noting, the proposals and goals that it already provides for the coming years.